Антология выдающихся достижений в науке и технике. Часть 34: Открытие и изучение квантово-волновой природы микромира материи - Баранов, М.И. (Електротехніка і електромеханіка, 2016)
Приведен краткий аналитический обзор основных научных достижений ученых в области открытия и изучения квантово-волновой природы физических процессов и явлений, протекающих в микромире окружающей нас материи. В число таких достижений вошли как ставшие классическими квантовые теории теплового излучения абсолютно черного тела, атома, фотоэлектрического эффекта и явления сверхтекучести жидкого гелия, так и современные открытия в области квантовой электроники и новейшие квантовомеханические результаты для дрейфа свободных электронов и их волновых распределений в проводниках электрических цепей с током Наведено короткий аналітичний огляд основних наукових досягнень вчених в галузі відкриття і вивчення квантовохвилевої природи фізичних процесів і явищ, що протікають в мікросвіті матерії, що оточує нас. У число таких досягнень увійшли як квантові теорії теплового випромінювання абсолютно чорного тіла, атома, фотоелектричного ефекту і явища надтекучості рідкого гелію, що стали класичними, так і сучасні відкриття в галузі квантової електроніки та новітні квантовомеханічні результати для дрейфу вільних електронів і їх хвилевих розподілів в провідниках електричних кіл із струмом. Purpose. Implementation of brief analytical review of the basic distinguished scientific achievements of the world scientistsphysicists in area of discovery and study of quantum-wave nature of physical processes and phenomena flowing in the microscopic world of circumferential people matter. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information in area of theoretical and experimental physics, devoted the results of researches of quantum and physical processes flowing in nature on atomic and subatomic levels. Results. The brief scientific and technical review of the basic scientific discovery and achievements of scientists-physicists is resulted in area of structure of atom of matter, generation, radiation, distribution and absorption of physical bodies of short-wave hertzian waves, indicative on a dominating role in the microscopic financial world of positions and conformities to the law of wave (by quantum) mechanics, carrying especially probabilistic character a microstructure. Originality. Systematization is executed with exposition in the short concentrated form of the known materials on the quantum theory (electromagnetic) of caloradiance, quantum theory of atom, electronic waves, quantum theory of actinoelectricity, quantum statistics of microparticless, quantum theory of the phenomenon superfluidity of liquid helium, quantum electronics and quantum-wave nature of drift of lone electrons in the metal of explorers with an electric current. Practical value. Popularization and deepening of fundamental physical and technical knowledges for students and engineer and technical specialists in area of classic and quantum physics, extending their scientific range of interests, and also support a further scientific study by them surrounding nature and to development of scientific and technical progress in society